Evaluating the implementation process of a new telerehabilitation modality in three rehabilitation settings using the normalization process theory: study protocol. (2nd October 2019) - Kairy, Dahlia; Messier, Frédéric; Zidarov, Diana; Ahmed, Sara; Poissant, Lise; Rushton, Paula W.; Vincent, Claude; Fillion, Brigitte; Lavoie, Véronique
ABSTRACT: Introducing innovations such as telerehabilitation (TR) into routine care involves complex changes in organizations. This study protocol aims to (1) examine the extent to which a TR platform was implemented as intended in three clinical settings and (2) identify which TR activities were becoming integrated into routine clinical practices, and which factors affect the routine use of the platform. A mixed-method prospective single-case study design with multiple embedded units of analysis will be used. Pre/post-implementation data collection will focus on implementation leaders, clinical champions, upper management, and clinical staff. Qualitative data include semistructured individual interviews with leaders, champions, and upper management as well as focus groups with clinical staff who are users and non-users of the TR platform. Quantitative data include TR use data and TR implementation questionnaires. The consolidated framework for implementation research will be used to analyze the implementation process and normalization process theory will be used to analyze the embedding of TR in routine daily practice. The project is expected to yield evidence regarding which specific TR activities are implemented in day-to-day clinical activities as well as capture threats and opportunities to normalization at a critical moment when it is expected to occur.